Biclique cryptanalysis on lightweight block ciphers I-PRESENT-80 and I-PRESENT-128 - Jie CUI; Hai-feng ZUO; Hong ZHONG (Tongxin xuebao)
I-PRESENT was a lightweight SPN block cipher for resource-constraint environments such as RFID tags and sensor networks.The biclique structures of I-PRESENT with sieve-in-the-middle technique was an constracted.The biclique cryptanalysis schemes on full-round I-PRESENT-80 and I-PRESENT-128 were proposed for the first time.The results show that the data complexity of the biclique cryptanalysis on I-PRESENT-80 and I-PRESENT-128 is 2 26 and 236 chosen ciphertexts respectively，and the time complexity on them is 2 79.48 and 2 127.33 encryptions respectively.The time and data complexity are better than that of the exhaustive attack.In addition,the time complexity on them can be reduced to 2 78.61 and 2126.48 encryptions by using related-key technology of I-PRESENT.